Pandangan Hak Asasi Manusia Terhadap Kebijakan Two Child Policy Presiden Xi-Jinping - Khairur Rizki; Muhammad Chandra Hariadi (Indonesian Journal of Peace and Security Studies (IJPSS), 2021)
People’s Republic of China (PRC) is one of the biggest countries in terms of its population. Which was the result of its people’s high fertility rate. The high rate of fertility creates an influx of birthrate, thus, increasing the population by a lot. But at the same time, it raises a new problem: China's economy can’t sustain the overly-grown population. China came with a new two-child policy, a policy dedicated to limiting the number of children a household could give birth to, a solution to cut out the influx of population. This, of course, sparked a wave of criticisms from the Western world. The West viewed; China’s policy as a breach of Human Rights as it limits its people’s freedom to give birth. This study uses a qualitative method which is descriptive analysis. The concept used is the concept of individual freedom in the form of Positive Liberty (positive freedom) and Negative Liberty (negative freedom). The results of the study, namely the Two-Child Policy, actually hurt human rights because people were forced to pay taxes if they had a second child with a value of almost 100 million rupiahs which eventually encouraged women to have abortions and sterilization. This policy also creates problems for those who wish to have more children. This policy is believed to be President Xi Jinping's effort to anticipate the slack in the Chinese labor supply due to the declining productive age population, so basically, this policy was issued not to side with human rights, but to safeguard China's economic interests